Association Between Organ Procurement Organization Social Network Centrality and Kidney Discard and Transplant Outcomes. Issue 12 (December 2015) - Butala, Neel M.; King, Marissa D.; Reitsma, William; Formica, Richard N.; Abt, Peter L.; Reese, Peter P.; Parikh, Chirag R.
Abstract : Background: Given growth in kidney transplant waitlists and discard rates, donor kidney acceptance is an important problem. We used network analysis to examine whether organ procurement organization (OPO) network centrality affects discard and outcomes. Methods: We identified 106, 160 deceased donor kidneys recovered for transplant from 2000 to 2010 in Scientific Registry of Transplant Recipients. We constructed the transplant network by year with each OPO representing a node and each kidney-sharing relationship between OPOs representing a directed tie between nodes. Primary exposures were the number of different OPOs to which an OPO has given a kidney or from which an OPO has received a kidney in year preceding procurement year. Primary outcomes were discard, cold-ischemia time, delayed graft function, and 1-year graft loss. We used multivariable regression, restricting analysis to the 50% of OPOs with highest discard and stratifying remaining OPOs by kidney volume. Models controlled for kidney donor risk index, waitlist time, and kidney pumping. Results: An increase in one additional OPO to which a kidney was given by a procuring OPO in a year was associated with 1.4% lower likelihood of discard for a given kidney (odds ratio, 0.986; 95% confidence interval, 0.974-0.998) among OPOs procuring high kidney volume, but 2% higher likelihood of discard (odds ratio, 1.021; 95% confidence interval, 1.006-1.037) among OPOs procuring low kidney volume, with mixed associations with recipient outcomes. Conclusions: Our study highlights the value of network analysis in revealing how broader kidney sharing is associated with levels of organ acceptance. We conclude interventions to promote broader inter-OPO sharing could be developed to reduce discard for a subset of OPOs. Abstract : Using network analysis, an increase in 1 additional organ procurement organization to which a kidney is given by an OPO with high-volume procurement is associated with 2% lower likelihood of discard for a given kidney, but 2% higher likelihood of discard among OPOs with low-volume procurement. There are mixed associations with recipient outcomes.